Using crossmodal correspondences as a tool in wine communication - Crichton-Fock, Anders; Spence, Charles; Pettersson, Nicklas (Frontiers in Psychology, 2023)
Introduction This research investigates consumer acceptance of alternative methods for communicating information about wine, focusing on the alignment between sensory attributes and consumer expectations. Methods A survey was administered to wine enthusiasts to assess their attitudes toward crossmodal communication. Results The findings reveal significant associations between consumer behaviors and acceptance of alternative communication methods, highlighting the emerging field of crossmodal correspondences. Discussion These results suggest that leveraging crossmodal correspondences can enhance the match between a product’s sensory qualities and consumer expectations, potentially reducing wine wastage resulting from unmet consumer preferences. These findings have implications for improving communication strategies in the wine industry and enhancing consumer experiences.